KAJIAN VEGETASI MANGROVE DI KABUPATEN BUTON UTARA (STUDI KASUS DI KECAMATAN KULISUSU) : Study of Mangrove Vegetation in North Buton District (Case Study in Kulisusu District) - satya laksananny; Erny Poedjirahajoe; Ris Hadi Purwanto; Muh. Taufik Tri Hermawan (Forestry Faculty of Universitas Hasanuddin, 2022)
One of the areas in Southeast Sulawesi Province and its potential mangrove forest ecosystem is North Buton Regency. The mangrove forest ecosystem in North Buton Regency is one of the coastal natural resources that have an essential role in social, economic and ecological aspects; besides, it also has the primary function as a balancer for the ecosystem. Provider of various necessities of life for humans and other living creatures. This study aims to determine the critical value index and mangrove density index in Eelahaji Village and Waculaeya Village, Kulisusu District, North Buton Regency. The research approach method uses vegetation analysis to determine the critical value index and the vegetation diversity index. The results showed that there were 5 (five) types of mangrove species in Eelahaji Village and Waculaeya Village, namely Bruguiera gymnorrhiza, Rhizophora stylosa, Xylocarpus granatum, Heritiera littoralis, Bruguiera parviflora. At the seedling and tree levels, the highest INP and H' in Eelahaji Village were B. gymnorrhiza, seedling INP level: 74; H': 0.4; INP tree level: 96 and H': 0.4.; The highest INP and H' at the pole or sapling level were R. stylosa species, namely INP: 105 and H': 0.4. The highest INP and H' in Waculaeya Village at the seedling level and the pole or sapling level were the B. gymnorrhiza species, namely the seedling level INP: 82; H': 0.4; at the level of piles or stakes INP: 97; H': 0.4, while the highest INP and H' tree levels were R. stylosa, namely INP: 100; H': 0.4. INP (importance value index) and H' (level of diversity) describe the density, frequency and dominance of mangrove vegetation in its ecosystem.